Corpus Linguistics As A Tool For Language Study - Boboniyozova Iroda Qurboniyozovna (Euro Asian Journal Publishing, 2024)
Corpus linguistics has revolutionized the study of languages, offering empirical insights into linguistic patterns, usage, and evolution. This article explores the methodologies and applications of corpus linguistics as a powerful tool for understanding linguistic phenomena. It highlights its role in lexicography, language teaching, sociolinguistics, and discourse analysis, emphasizing its potential to bridge theory and practice in language research.
Keywords: Corpus linguistics; linguistic patterns; language teaching